Kompetensi Mahasiswa Praktik Kerja Lapangan di Perbankan Syariah: Studi Mahasiswa Jurusan Syariah Program Studi Muamalah Sekolah Tinggi Agama Islam Negeri Samarinda - Akhmad Nur Zaroni (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2014)
The objective of this study is to describe the students’ competency of Muamalah study program of STAIN Samarinda who were conducting school internship program at three Syariah Banks in Samarinda. The banks are Bank Muamalat Indonesia, Bankaltim Syariah, and Bank Syariah Bukopin. The competency, here, are basic competency, managerial competency, and operational/technical competency. This is a descriptive research design. The result of the study shows that the students’ competency of Muamalah study program of STAIN Samarinda is 7.85% or it is classified as “Good”. The overall findings are: basic competency is 77,27% (Good), operational competency is 69,55% (Good), and managerial competency is 68,73% (Fair). There are 2 of 28 indicators which have the highest score, they are moral integrity and the understanding of the concept of syariah economy; the score is 83.64% for each category which is classified as “Very Good”. Meanwhile, there three aspects which have the lowest score, they are: presentation skill, human relations, and carefulness to the jobs. The score is 56.36% for each category which is classified as “Fair”.